Home Occupant Archetypes - Marco Antonio ORTIZ SANCHEZ (A+BE: Architecture and the Built Environment)
This research is aimed at better understanding how occupants use energy in their homes from a comfort-driven perspective, in order to propose customized environmental characteristics that could improve the occupants’ comfort while reducing energy consumption. To propose such bespoke environmental features and feedback, occupant archetypes were produced based on the intentions and motivations behind comfort behaviours. Building upon the aim of this thesis, the following main research question was proposed: